Permanence and Global Attractivity of Discrete Predator-Prey System with Hassell-Varley Type Functional Response - Runxin Wu; Lin Li (Discrete Dynamics in Nature and Society)
By constructing a suitable Lyapunov function and using the comparison theorem of difference equation, sufficient conditions which ensure the permanence and global attractivity of the discrete predator-prey system with Hassell-Varley type functional response are obtained. Example together with its numerical simulation shows that the main results are verifiable.